Energy conversion and balance of grain production systems with pastures under no-tillage - Santos, Henrique Pereira dos; Fontaneli, Renato Serena; Ignaczak, João Carlos; Zoldan, Sandra Maria (Pesquisa Agropecuaria Brasileira, 2000)
Data obtained from experiments conducted, from 1990 to 1995, at the Universidade de Passo Fundo, Rio Grande do Sul State, Brazil, were evaluated with the objective to study the energy conversion and balance of four grain production systems with annual winter pastures. Four grain production systems were evaluated: system I (wheat/soybean, black oats/soybean, and black oats/soybean); system II (wheat/soybean and black oats + common vetch/corn); system III (wheat/soybean, black oats + common vetch/soybean, and black oats + common vetch/corn); and system IV (wheat/soybean, white oats/soybean, and white oats/soybean). Both winter and summer crops were grown under no-tillage. The trial was set up blocks at random, with three replications and plots with 500 m2. Systems II and III showed higher energy conversion (5.78 and 5.44) and balance rates (23,728 and 21,741 kg/Mcal), as compared to systems I (3.79 and 11,553 kg/Mcal) and IV (4.33 and 12,879 kg/Mcal), respectively. It was evident that the integration crop-livestock under no-tillage is a viable system, since the energetic conversion and balance showed positive results; actually, these rates were significantly higher in the systems including corn crop.